Di-Genic Inheritance in Genodermatoses: Insights from Two Consanguineous Cases in a Reference Lebanese Center within the Middle East and North Africa (MENA) Region - Ayat Kadhi; Lamiaa Hamie; Edward Eid; Georges Nemer; Mazen Kurban (Dermatology Practical & Conceptual)
Introduction: Genodermatoses refer to a group of heterogenous rare genetic diseases with cutaneous expression. Several genodermatoses present with multisystem involvement that can range from mild to life-threatening conditions leading to increased morbidity and mortality.